2022
DOI: 10.1021/acs.chemrev.2c00356
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of Alloys: Classification, Principles, and Design for a Variety of Materials and Reactions

Abstract: Alloying has long been used as a promising methodology to improve the catalytic performance of metallic materials. In recent years, the field of alloy catalysis has made remarkable progress with the emergence of a variety of novel alloy materials and their functions. Therefore, a comprehensive disciplinary framework for catalytic chemistry of alloys that provides a cross-sectional understanding of the broad research field is in high demand. In this review, we provide a comprehensive classification of various a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(103 citation statements)
references
References 835 publications
(1,554 reference statements)
0
102
0
1
Order By: Relevance
“…For the vinyl on the hollow, the coordinating carbon atom was off-centered to be slightly far from the Cu atom, resulting in a "2.5-fold-like" state and signi cant destabilization. This trend indicated that the ensemble effect by Cu e ciently tuned the adsorptivity 24 . Moreover, the minute energy change for the on-top adsorption on Ni suggested that the contribution of the ligand effect of Cu on Ni was extremely minor.…”
Section: Resultsmentioning
confidence: 91%
“…For the vinyl on the hollow, the coordinating carbon atom was off-centered to be slightly far from the Cu atom, resulting in a "2.5-fold-like" state and signi cant destabilization. This trend indicated that the ensemble effect by Cu e ciently tuned the adsorptivity 24 . Moreover, the minute energy change for the on-top adsorption on Ni suggested that the contribution of the ligand effect of Cu on Ni was extremely minor.…”
Section: Resultsmentioning
confidence: 91%
“…25,32 One major benefit of forming an alloy is to provide adjustment of the surface electronic structures of the catalysts, leading to optimized binding between the catalyst surfaces and key intermediates of the electrocatalytic reactions. [35][36][37][38] For example, metals have different adsorption energies towards the *OH species, which is the key intermediate during oxygen reduction reactions (ORRs). 36,39 And although Pt and Pd are the best ORR catalyst candidates, the adsorption energies of *OH on these metals are still not optimized according to the volcano plot.…”
Section: Hui Jinmentioning
confidence: 99%
“…Intermetallic compounds (IMCs), some of the binary alloys, have well-ordered atom arrangements in their crystal structures, being recognized as standout electrochemical , and thermal catalysts − for various reactions. This is because their surface atom arrangements are expected to be regular in each of their facets corresponding to Miller indices, which originates from their well-ordered crystal structures.…”
Section: Introductionmentioning
confidence: 99%